The Modern Cryobank as Key Support for Clinical Cell and Tissue Transplantation Programmes - Měřička, Pavel; Jandová, Miroslava; Fuller, Barry; Gregor, Jiří; Studená, Šárka; Lánská, Miriam; Vokurková, Doris; Jankovičová, Karolína; Fátorová, Ilona; Brandejs, Daniel; Guňka, Igor; Benda, Aleš; et al. (Problems of Cryobiology and Cryomedicine, 2024)
The authors review the essential role of modern cryobanks in the development of cryotechnology before the start of the clinical cell and tissue transplantation programme and in the routine support of these programmes within the legislative framework settled by the European Union directives. Two clinical programmes are presented as examples: the autologous and allogeneic haematopoietic progenitor cell (HPC) transplantation programme and the Czech national cryopreserved allogeneic vascular tissue (VT) transplantation programme supported by the cryobank of the University Hospital Hradec Králové, which is a part of the European Union Tissue Establishment registered under the codes CZ000425, CZ000426 and CZ000427. An overview of necessary approvals to be obtained before the start of clinical programmes is presented, the high quality of cryopreservation technology and high level of cryobank staff safety is demonstrated, and the crucial role of the cryobank in clinical HPC and VT transplantation programmes is highlighted. Probl Cryobiol Cryomed 2024; 34(2):71–112